Essays on Corporate Loans and Credit Risk - Pia Mølgaard (Copenhagen Business School (CBS), 2018)
Classical asset pricing theory assumes markets" which means that nancial markets are frictionless. However, in the real world nancial frictions exists. Recently the nancial literature has focused more on these frictions and on how they a ect asset prices. This thesis contributes to the literature by providing evidence on how nancial frictions a ect pricing and trading of corporate loans. The rst chapter examines how managers of collateralized loan obligations (CLOs) trade leveraged loans and how their activity a ects the performance of the CLO. The second chapter examines how the performance of leveraged loans depends on the borrowers' relationship with its bank. The third chapter studies methodologies used to quantify how information ows between the corporate bond and the credit default swap market.
hdl:10398/9674
Keywords: 650